The gingerbread architect : recipes and blueprints for twelve classic American homes - Matheson, Susan; Chattman, Lauren; Grablewski, Alexandra (New York : Clarkson Potter, 2008)
Contains blueprints and elevations for gingerbread houses based on twelve classic American homes, and includes baking directions, construction notes, and recipes.
Includes index.
Adult
Keywords: Gingerbread houses; Gingerbread houses